2017
DOI: 10.1161/circulationaha.117.030972
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-Derived 3-Hydroxyanthranilic Acid Contributes to Angiotensin II–Induced Abdominal Aortic Aneurysm Formation in Mice In Vivo

Abstract: Background Abnormal amino acid metabolism is associated with vascular disease. However, the causative link between dysregulated tryptophan metabolism and abdominal aortic aneurysm (AAA) is unknown. Methods Indoleamine 2,3-dioxygenase (IDO) is the first and rate-limiting enzyme in the kynurenine pathway of tryptophan metabolism. Mice with deficiencies in both apolipoprotein e (Apoe) and IDO (Apoe−/−/IDO−/−) were generated by cross-breeding IDO−/− mice with Apoe−/− mice. Results The acute infusion of angiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 59 publications
0
69
0
Order By: Relevance
“…Aneurysm formation was associated with an accumulation of macrophages and T lymphocytes within the adventitia and the media, but no significant differences were observed between AngII-infused Ldlr -/- Ido1 +/+ and Ldlr -/- Ido1 -/- mice ( Fig 2A and 2B ). A recent study reported that IDO promoted aneurysm formation through 3HAA production, which activated MMP2 expression[ 12 ]. Therefore, we investigated MMP expression and activity in our model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aneurysm formation was associated with an accumulation of macrophages and T lymphocytes within the adventitia and the media, but no significant differences were observed between AngII-infused Ldlr -/- Ido1 +/+ and Ldlr -/- Ido1 -/- mice ( Fig 2A and 2B ). A recent study reported that IDO promoted aneurysm formation through 3HAA production, which activated MMP2 expression[ 12 ]. Therefore, we investigated MMP expression and activity in our model.…”
Section: Resultsmentioning
confidence: 99%
“…Angiotensin (Ang) II, widely used to induce dissecting aortic aneurysm [ 10 ], was previously shown to increase IDO activity through the production of mitochondrial reactive oxygen species [ 11 ]. Moreover, a recent report indicates that IDO deficiency in AngII-infused apolipoprotein e-deficient ( Apoe -/- ) mice protects against AAA[ 12 ]. The authors attributed the pro-aneurysmal effect of IDO to one of the Kyn-derived metabolites, 3-hydroxyanthranilic acid (3-HAA), which induced aneurysm by increasing MMP-2 expression in VSMC[ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximal outer diameter of the suprarenal aorta was measured by the ImageJ software (Wayne Rasband, National Institutes of Health, Bethesda, MD). An aneurysm was defined as ≥50% dilation of the outer diameter, as compared to the suprarenal aortae of mice in the control group (Q. Wang et al, ). AAA formation was classified into four types, as described by Daugherty, Cassis, and Lu (): Type I is a small, single dilation that is 1.5–2.0 times greater than normal; Type II is a large, single dilation that is more than 2.0 times larger than normal diameter; Type III is multiple dilations; and Type IV is an aortic rupture that results in death due to bleeding into the peritoneal cavity.…”
Section: Methodsmentioning
confidence: 99%
“…IDO is a unique immune checkpoint protein by promoting tryptophan degradation via the kynurenine pathway and can be blocked using small molecule inhibitors. By converting tryptophan to kynurenine, IDO promotes immune suppression via two distinctive molecular mechanisms, 1) depletion of an essential amino acid, tryptophan, to activate cellular stress pathways via GCN2 [50] and 2) generating downstream immune suppressive metabolites such as 3hydroxyanthranillic acid [51] and xanthurenic acid [52]. Details of these mechanisms are extensively discussed in reviews [53]; thus we will not discuss this further due to the space limitation.…”
Section: The Influence Of Immunosuppressive Tumor Microenvironment (Tmentioning
confidence: 99%